The Pengembangan E-Modul Sintesis Metal Organic Frameworks Cu-BDC Sebagai Adsorben Zat Warna Berbasis Problem Based Learning Untuk Meningkatkan Literasi Sains Mahasiswa - Septika Amalia Umaro; Sura Menda Ginting; M. Lutfi Firdaus (UNIB Press, 2024)
This research aimed to analyze the feasibility of an e-module with the topic of synthesis of Metal Organic Frameworks (MOFs) Cu-BDC as adsorbents for Congo red and Metanil yellow dyes, as well as to analyze the improvement of students' scientific literacy after the implementation of a Problem Based Learning-based e-module in the material chemistry course using a Telegram bot application. The research method used was research and development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included observation, tests, and questionnaires. The research instruments consisted of test sheets and questionnaires that have been validated by experts. Data analysis technique used was quantitative analysis. Based on the validation results of the e-module by content experts, a score of 93.17% was obtained, media experts 95.8%, test validation results 88.75%, and student response questionnaire validation results 92.6%. Overall, it can be concluded that the validation results of the e-module fall under the category of very feasible. The student response questionnaire towards the e-module resulted in a score of 95% with a category of very feasible. The n-gain result obtained after the application of the e-module in the material chemistry course is 0.67 with moderate criteria. In conclusion, the e-module with the topic of synthesis of MOFs Cu-BDC as adsorbents for Congo red and Metanil yellow dyes using Problem Based Learning model and Telegram bot application is highly suitable for use as an alternative teaching material in the material chemistry learning process and can improve students' scientific literacy.